(untitled) (Justicia &Derecho, 2025)
In the present research article, we will examine the legal nature of certain significant “penalties” that the Administration may impose on the contractor for non-compliance within an administrative contract for Public Works. To this end, an exegetical analysis of DFL 850 dated February 25, 1998, from the Ministry of Public Works and its corresponding Regulations will be conducted. Subsequently, an empirical analysis will be undertaken to determine the interpretation given by the Administration to these sanctions. Finally, a jurisprudential analysis will be carried out to determine which of these measures strictly have an Administrative Penalty nature, coercive fine, or indemnity character.